(untitled) (Pravaha, 2025)
To the author’s best knowledge, it was the first study of variables determining the investor opinion on hydropower equity in Nepal, encompassing economic, social, environmental, and technological aspects. Therefore, with the employment of the structured questionnaire and statistical analysis, the question to be answered was: which of the specified factors determine the investor opinion regarding hydropower industry the most? It appears that economic aspects were the most critical variable, while ROI and government incentives indeed affected the likelihood of a favorable opinion. Social variables, community acceptance, and corporate social responsibility relevantly grew in the existing literature, which is consistent with SRI trend. Nevertheless, it could be posited that environmental factors -practices or compliance- represent the most paramount factor. Similarly, investor perceptions are minimally affected by consideration of technological factors since integration is still at an infancy stage in the Nepal hydropower industry, hence why technological factors do not appear to have an impact. The study revealed that economic stability, social responsibility and sustainability are significant considerations in establishing investor perceptions whilst technological factors are not a significant characteristic at this stage. Overall, the implications arising from these findings are substantial for investor investors and stakeholders, including policy makers or those potentially interested in attracting investor investment into hydropower projects.